Development of life cycle water footprints for oil sands-based transportation fuel production. (15th July 2017) - Ali, Babkir; Kumar, Amit
Abstract: There is considerable focus on oil sands transportation fuel production. However, most studies focus on greenhouse gas emissions; there is limited work on understanding the life cycle water footprint. This study is an effort to address this gap. The main objective of this study is to develop water demand coefficients of the complete life cycle of oil sands transportation fuel production. Water demand coefficients include consumption and withdrawals, which were estimated for different oil sands unit operations pathways for production in Alberta, Canada. The pathways include three key operations, bitumen extraction, upgrading, and refining. The water consumption coefficients for the complete life cycle range from 2.08 to 4.19 barrels of water (bblW ) per barrel of refined oil (bblBUR ) and 2.87–5.16 bblW /bblBUR for water withdrawals coefficients. The lower limit for water demand coefficients is found in refined and upgraded in situ steam assisted gravity drainage recovery and the higher amount in refined and upgraded surface mining recovery. A sensitivity analysis was conducted through Monte Carlo simulations to study the uncertainty of the water demand coefficients. The water consumption coefficient for oil sands extraction at a 90% probability was found to be 0.34–2.8 bblW /bblB, upgrading be 0.87 bblW /bblU, and refining to be 1.52 bblW /bblR . Highlights: The life cycle water footprint for oil sands-based transportation fuel was studied. Water footprints for bitumen extraction, upgrading, and refining were developed. The water consumption coefficients for the complete life cycle of oil sands ranges from 2.08 to 4.19 bbl/bbl refined oil. Surface mining has a higher water consumption coefficient than steam-assisted gravity drainage.